A non-fired ceramsite construction material with enhanced lightweight high strength properties. (31st March 2023) - Hu, Guangchao; Yan, Kezhou; Gao, Jian-ming; Cheng, Fangqin; Huo, Xiangtao; Guo, Min; Zhang, Mei
Graphical abstract: Highlights: The ceramsite was prepared by low-activity circulating fluidized bed fly ash (CFBFA) with 73% utilization. The ceramsite was non-fired without pretreating CFBFA. The ceramsite behaved the strength of 5.5 MPa and porosity of 51.86 % synchronously. Both quicklime and desulfurized gypsum can promote the formation of CSH in the system. The preparation process is simple, green and energy-saving. Abstract: The combustion of low calorific value coal in circulating fluidized bed boilers produces a large amount of fly ash with low activity and utilization. In this paper, the lightweight high strength ceramsite was prepared by a non-fired method using low-activity circulating fluidized bed fly ash (CFBFA) as raw material. And the effects of reinforcing agent and foaming agent on the properties of ceramsite were studied. The dosages of cement, quicklime, desulfurization gypsum and hydrogen peroxide were 15.0 wt%, 6.0 wt%, 6.0 wt% and 2.0 wt%, respectively. The hydration reaction in the system can be maximized by steam curing at 70 ℃ for 12 h. The bulk density and cylinder compressive strength of the obtained ceramsite were 695.34 kg/m 3 and 5.5 MPa, respectively, which belonged to 700 grade high strength fly ash ceramsite. The corresponding apparent density and apparent porosity of the products were 1091.88 kg/m 3 and 51.86 %, respectively. The admixture of cement, quicklime and desulfurization gypsum can all promote the hydration reaction in the system to produce denser needle-like and flocculent CSH. In addition, the admixture of hydrogen peroxide only enhanced the porosity of ceramsite and had no effect on the phase. The experimental process was simple, green and energy saving. In particular, the total solid waste utilization was up to 79 %.